The effect of tourist destination attractiveness, customer experience, and service form on return visit interest using tourist satisfaction in pujon kidul tourist village - Atyanta Rahma Mahiru; Respati Hariyanto; Andini Risfandini (Jurnal Pariwisata Pesona, 2024)
Tourist Destination Attraction, Customer Experience, Servicescape and visitor satisfaction can influence the interest of tourists to revisit the tourist attraction, efforts that have been made by Pujon Kidul Tourism Village are conducting several promotional activities through print media and the internet. The purpose of this study is: To determine the effect of Tourist Destination Attraction, Customer Experience and Servicescape on Tourist Satisfaction in Pujon Kidul Tourism Village. To determine the effect of Tourist Destination Attraction, Customer Experience and Servicescape on Tourist Revisit Interest in Pujon Kidul Tourism Village. To determine the effect of Tourist Satisfaction on Interest in Revisiting Pujon Kidul Tourism Village. To determine the effect of Tourist Destination Attraction, Customer Experience and Servicescape on Interest in Revisiting through Tourist Satisfaction in Pujon Kidul Tourism Village. The approach used in this study is a quantitative approach, especially the type of research that uses an explanatory approach to explain the relationship and emphasizes the analysis of numerical data cause and effect on service quality and competitive advantage on tourist satisfaction using questionnaire techniques. The results of the study indicate that there is a partial positive and significant influence of the Attraction of Tourist Destinations, Customer Experience and Servicescape on the Interest of Returning Tourists to Pujon Kidul Tourism Village. The results of the study indicate that there is a partial positive and significant influence of Tourist Satisfaction on the Interest of Returning to Pujon Kidul Tourism Village. The results of the study indicate that there is a partial positive and significant influence of the Attraction of Tourist Destinations, Customer Experience and Servicescape on the Interest of Returning through Tourist Satisfaction in Pujon Kidul Tourism Village.